2018
DOI: 10.3892/etm.2018.6535
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinone‑4 modulates the expression levels of calcification‑associated factors to inhibit calcification of rat aortic vascular smooth muscle cells in a dose‑dependent manner

Abstract: Vascular calcification (VC) caused by chronic kidney disease (CKD)-mineral and bone disorder is a common complication of CKD. Recent studies have demonstrated that menaquinone-4 (MK-4) is negativly associated with VC in patients with CKD. Furthermore, we have previously shown that runt-related transcription factor 2 (Runx2) is important in the phenotypic transformation process of rat vascular smooth muscle cells (VSMCs), which is the key step for the development of VC. The present study investigated the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
7
1
1
Order By: Relevance
“…The inhibitory role of combined PB and vitamin K2 can be explained via a mechanism other than MGP activation. It has been shown that vitamin K protects VSMC differentiation and calcification into an osteogenic phenotype under a high phosphate environment via downregulation of bone-specific genes [37,38]. However, we could not find such an effect in our study (data not shown).…”
Section: Discussioncontrasting
confidence: 86%
“…The inhibitory role of combined PB and vitamin K2 can be explained via a mechanism other than MGP activation. It has been shown that vitamin K protects VSMC differentiation and calcification into an osteogenic phenotype under a high phosphate environment via downregulation of bone-specific genes [37,38]. However, we could not find such an effect in our study (data not shown).…”
Section: Discussioncontrasting
confidence: 86%
“…The latter is secreted by VSMCs and inhibits VC through poorly studied mechanisms [ 53 ]. These findings support a protective role for vitamin K in VC and this has been confirmed by numerous other studies [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Role Of Nuclear Receptors In Vascular Calcificationsupporting
confidence: 89%
“…Vitamin K2 has several different vitamers or menaquinones (MK), of which MK4-MK7 can exert important biologic actions. In-vitro, MK4 has been shown to act as an inhibitor of VC in vascular smooth muscle cells (VSMCs) (30,31). Furthermore, in HD patients, Fusaro et al showed that MK4 deficiency emerged as a significant predictor of aortic calcifications (24).…”
Section: Introductionmentioning
confidence: 99%